ANALISIS RESIKO HUBUNGAN KINERJA RUAS JALAN DENGAN TINGKAT KEBISINGAN PADA KAWASAN PENDIDIKAN SMA/SMK YADIKA BANDAR LAMPUNG - Khanza, Ayu Kamila; Michael, Michael (Yayasan Nusantara Hasana Berdikari, 2025)
The increase in the number of vehicles in Indonesia, particularly in Bandar Lampung, has led to higher traffic flow, which potentially causes various transportation issues, one of which is noise pollution. ZA. Pagar Alam Street, a primary arterial road in Bandar Lampung, is one of the main routes with heavy traffic, especially in educational areas. One of the schools located along this road is SD Negeri 1 Labuhan Ratu, which is likely to be affected by noise pollution from the high traffic volume. This study aims to analyze the impact of traffic flow and vehicle speed on noise levels in the school environment and compare the measurement results with the noise threshold set by the Minister of Environment Decree No. KEP-48/MENLH/1996, which is 55 dB for educational areas. Measurements were conducted using a Sound Level Meter over three days—Monday, Thursday, and Saturday—from 07:30 to 12:30, representing traffic conditions on regular school days and weekends.The findings of this study are expected to provide an overview of noise levels in educational areas and serve as a reference for mitigating the impact of noise pollution in schools located near major roads.